2020
DOI: 10.2196/preprints.18275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Internet-delivered vs face-to-face cognitive behavior therapy for anxiety disorders: systematic review and meta-analysis (Preprint)

Abstract: BACKGROUND Over the last twenty years, Internet-delivered cognitive behavior therapy (ICBT) has been tested in a large number of randomized controlled trials, often with positive results. However not widely known about the efficacy of ICBT as compared to face-to-face cognitive behavior therapy (CBT). In the present systematic review and meta-analysis, ICBT for anxiety disorders were directly compared to face- to-face CBT within the same trial. This study aimed to reinvestigate the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
1
12
1
Order By: Relevance
“…However, we do not believe that this affected our results substantially, given previous research suggesting that the additive effect of using databases other than PubMed is modest in the therapeutic field 46 . Also, in a recently conducted meta‐analysis of ICBT vs. face‐to‐face CBT for anxiety disorders – in which the authors used Scopus, Emerald, ProQuest, and Science Direct in addition to PubMed to identify studies – no additional studies compared to our meta‐analysis were included 47 .…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not believe that this affected our results substantially, given previous research suggesting that the additive effect of using databases other than PubMed is modest in the therapeutic field 46 . Also, in a recently conducted meta‐analysis of ICBT vs. face‐to‐face CBT for anxiety disorders – in which the authors used Scopus, Emerald, ProQuest, and Science Direct in addition to PubMed to identify studies – no additional studies compared to our meta‐analysis were included 47 .…”
Section: Discussionmentioning
confidence: 99%
“…An online therapist guides the patient and provides them with appropriate support by monitoring progress, clarifying information and helping the patient to access the appropriate treatment steps. 51 Various forms of iCBT have been designed by researchers worldwide. In most cases, a therapist guides the patient during the entire CBT process.…”
Section: Overview Of Cbtmentioning
confidence: 99%
“…Internet-delivered treatment for GAD was effective for anxiety, worry, depression, functional impairment and quality of life [48,49]. A meta-analysis showed that internet-delivered cognitive behaviour therapy (ICBT) and face-to-face CBT created similar effects in treating anxiety disorders [50]. ICBT can significantly reduce SAD symptoms, and ICBT and face-to-face CBT produce equivalent results [51,52].…”
Section: Technology-delivered Therapymentioning
confidence: 99%